REWARD DAN PUNISHMENT DALAM PERSPEKTIF PENDIDIKAN ISLAM - Hidayati Siregar; Muhammad Syaifullah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Reward or praise has many purposes in the learning process, but the most important is to reinforce appropriate behavior and provide positive feedback to students who have done something right. Punishment is an act of sanction given to students who violate the rules. This study aims to describe the principles and forms of reward and punishment in the perspective of Islamic education. The method used in this research is the literature review method by exploring various reference sources in the form of books and journals. Reward (prize/prize) and punishment (punishment) is a method that is widely used in Islamic education. In order for the use of the reward and punishment method to be effective and efficient in Islamic education, there are several principles practiced by the Prophet Muhammad and should be emulated, namely: 1. Patience, tenacity, and determination in upholding Islamic teachings, 2. Forgiveness, without grudges and envy towards other people who do wrong to him, 3. Love and care for fellow believers. 4. Done proportionally and fairly and 5. Gradually and in line with the Shari'a. Rewards can be done in verbal form in the form of words or sentences of praise and in non-verbal form in the form of material gifts. While the form of punishment can be in the form of preventive punishment and repressive punishment.